Complete inhibition of ABCB1 and ABCG2 at the blood–brain barrier by co-infusion of erlotinib and tariquidar to improve brain delivery of the model ABCB1/ABCG2 substrate [11C]erlotinib. Issue 7 (July 2021) - Tournier, Nicolas; Goutal, Sebastien; Mairinger, Severin; Hernández-Lozano, Irene; Filip, Thomas; Sauberer, Michael; Caillé, Fabien; Breuil, Louise; Stanek, Johann; Freeman, Anna F; Novarino, Gaia; Truillet, Charles; et al.
P-glycoprotein (ABCB1) and breast cancer resistance protein (ABCG2) restrict at the blood–brain barrier (BBB) the brain distribution of the majority of currently known molecularly targeted anticancer drugs. To improve brain delivery of dual ABCB1/ABCG2 substrates, both ABCB1 and ABCG2 need to be inhibited simultaneously at the BBB. We examined the feasibility of simultaneous ABCB1/ABCG2 inhibition with i.v. co-infusion of erlotinib and tariquidar by studying brain distribution of the model ABCB1/ABCG2 substrate [ 11 C]erlotinib in mice and rhesus macaques with PET. Tolerability of the erlotinib/tariquidar combination was assessed in human embryonic stem cell-derived cerebral organoids. In mice and macaques, baseline brain distribution of [ 11 C]erlotinib was low (brain distribution volume, V T, brain < 0.3 mL/cm 3 ). Co-infusion of erlotinib and tariquidar increased V T, brain in mice by 3.0-fold and in macaques by 3.4- to 5.0-fold, while infusion of erlotinib alone or tariquidar alone led to less pronounced V T, brain increases in both species. Treatment of cerebral organoids with erlotinib/tariquidar led to an induction of Caspase-3-dependent apoptosis. Co-infusion of erlotinib/tariquidar may potentially allow for complete ABCB1/ABCG2 inhibition at the BBB, while simultaneously achieving brain-targeted EGFR inhibition. Our protocol may be applicable to enhance brain delivery of molecularly targeted anticancer drugs for a more effective treatment of brain tumors.